Letter - Winstanley, E.
030-0138-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. Our reference EXPORT ST/HP. 1179 Your reference 27th June, 1938. The Trades Union Congress, Transport House, Smith Square, LONDON. Dear Sirs, Our attention has been drawn to a statement in a recent issue of the Manchester Guardian, to the effect that at the Congress of the Amalgamated Union of Engineers dealing with relief for Spain, a sum of 50,000 was voted for this purpose. It has occurred to us that the Amalgamated Union might be interested in certain classes of goods we are producing, and are in fact already sending to Spain for relief purposes, and that consequently, the Amalgamated Union might be prepared to give us the opportunity of quoting for their requirements. At the same time, we also realise that this relief fund may come within your jurisdiction, and we would welcome any information regarding this matter with which you might be in a position to furnish us, and thanking you in anticipation, remain, Yours faithfully, E. Winstanley Export Department. 292/946/30/138